Pengaruh Interpass-temperature pada Pengelasan SMAW Terhadap Deformasi dan Kekuatan Impak Baja ASTM A36 - Muhammail, Muhammail; Saifudin, Saifudin; Habibi, Ilham (Borobudur Engineering Review, 2024)
Currently, welding is still very necessary for the increasingly advanced development of technology in the construction sector because it plays an important role in metal engineering and maintenance. This research aims to determine the effect of interpass temperature on deformation of weld results in ASTM A36 steel material. The method used in this research is an experimental method by measuring the deformation of the welded specimen. There are 9 specimens, the welding process uses shielded metal arc welding (SMAW), direct current reverse polarity (DCRP) with interpass temperature variations of 75 °C, 100 °C and 150 °C. The measurement results show deformation values ​​of 2.2°, 3.5° and 4° for each of the interpass temperatures of 75 °C, 100 °C and 150 °C. From the results of impact testing on specimens with interpass temperatures of 75 °C and 100 °C, it shows mixed fracture, namely brittle fracture and ductile fracture. The results of impact testing on specimens with an interpass temperature of 150 °C showed brittle fracture. The highest strength was at interpass temperature specimen of 100 °C, that is 211.79 Joules. And the lowest impact strength occurred in the interpass temperature specimen at 150 °C, that is 183.16 Joules.